Primary chemoablation of low-grade upper tract urothelial carcinoma using UGN-101, a mitomycin-containing reverse thermal gel (OLYMPUS): an open-label, single-arm, phase 3 trial. Issue 6 (June 2020) - Kleinmann, Nir; Matin, Surena F; Pierorazio, Phillip M; Gore, John L; Shabsigh, Ahmad; Hu, Brian; Chamie, Karim; Godoy, Guilherme; Hubosky, Scott; Rivera, Marcelino; O'Donnell, Michael; Quek, Marcus; et al.
Summary: Background: Most patients with low-grade upper tract urothelial cancer are treated by radical nephroureterectomy. We aimed to assess the safety and activity of a non-surgical treatment using instillation of UGN-101, a mitomycin-containing reverse thermal gel. Methods: In this open-label, single-arm, phase 3 trial, participants were recruited from 24 academic sites in the USA and Israel. Patients (aged ≥18 years) with primary or recurrent biopsy-proven, low-grade upper tract urothelial cancer (measuring 5–15 mm in maximum diameter) and an Eastern Cooperative Oncology Group performance status score of less than 3 (Karnofsky Performance Status score >40) were registered to receive six instillations of once-weekly UGN-101 (mitomycin 4 mg per mL; dosed according to volume of patient's renal pelvis and calyces, maximum 60 mg per instillation) via retrograde catheter to the renal pelvis and calyces. All patients had a planned primary disease evaluation 4–6 weeks after the completion of initial therapy, in which the primary outcome of complete response was assessed, defined as negative 3-month ureteroscopic evaluation, negative cytology, and negative for-cause biopsy. Activity (complete response, expected to occur in >15% of patients) and safety were assessed by the investigator in all patients who received at least one dose of UGN-101. Data presented are from the data cutoff on May 22, 2019. This study is registered with ClinicalTrials.gov, NCT02793128 . Findings: Between April 6, 2017, and Nov 26, 2018, 71 (96%) of 74 enrolled patients received at least one dose of UGN-101. 42 (59%, 95% CI 47–71; p<0·0001) patients had a complete response at the primary disease evaluation visit. The median follow-up for patients with a complete response was 11·0 months (IQR 5·1–12·4). The most frequently reported all-cause adverse events were ureteric stenosis in 31 (44%) of 71 patients, urinary tract infection in 23 (32%), haematuria in 22 (31%), flank pain in 21 (30%), and nausea in 17 (24%). 19 (27%) of 71 patients had study drug-related or procedure-related serious adverse events. No deaths were regarded as related to treatment. Interpretation: Primary chemoablation of low-grade upper tract urothelial cancer with intracavitary UGN-101 results in clinically significant disease eradication and might offer a kidney-sparing treatment alternative for these patients. Funding: UroGen Pharma.